PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BANGUN RUANG (BARUNG) BERBASIS ARTICULATE STORYLINE 3 PADA MATA PELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR - Hilma Rosikho Aliya; Wawan Priyanto; Riris Setyo Sundari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop interactive mathematics learning media based onArticulate Storyline 3 on spatial material for fifth grade elementary school students.The background to this research is students' low understanding of thecharacteristics of spatial structures due to learning which is still conventionalwithout the support of interesting media. This research uses the Research andDevelopment (R&D) method with the ADDIE development model which includesfive stages: Analyze, Design, Develop, Implement, and Evaluate. The datacollection instrument is a validation sheet whose validity has been tested by mediaexperts and material experts. The practicality test is in the form of a teacherresponse questionnaire and a student questionnaire to measure the practicality ofthe media that has been developed. The validation results show that the mediaobtained an average score of 0.71 (valid), and the material obtained a score of0.89 (very valid). Meanwhile, the practicality of the media based on studentresponses reached 84.16% (very practical) and teachers 100% (very practical).Thus, the interactive learning media &